Implementasi Flow Sensor untuk Monitoring Debit Air pada Proses Pengisian Air Galon Air pada Proses Pengisian Air Galon - Rouhillah; Inzar Salfikar; Andrian Maulana (Politeknik Aceh, 2025)
Automatic monitoring of water volume during gallon filling is a technology increasingly important in the water filling industry, particularly for ensuring accuracy and efficiency in the distribution process. This tool aims to monitor the water flow rate during the filling of mineral water gallons using a Flow Sensor. An Arduino Uno serves as the controller for this system. When the water pump is activated to fill the gallon, the flow sensor measures the amount of water flowing through it by generating pulses, which are then sent to the Arduino Uno for processing and calculation of the water flow rate. The results of these calculations are displayed on an LCD screen, stored in EEPROM memory for long-term data recording, and can be monitored remotely via a smartphone. This gallon water filling tool has a system accuracy percentage of 98%.